When the threat system is turned on: The impact of anger and shame on paranoia - Castilho, Paula (2015)
This paper aims to understand the nature of anger response and explore the relationship between anger, shame, depression and paranoia beliefs. Firstly, this study analyzed the contribution of the external shame and depression to the prediction of the components of anger. Secondly, it investigated the contribution of anger, external shame and depression to the prediction of paranoia. The sample consists of 208 individuals from community population, with a mean age of 32.67 (SD = 11.15) and years of education mean of 13.60 (SD = 3.97). Results show that external shame and depressive symptoms have a significant and an independent contribution for current feelings of anger (state-anger) and for expression of anger toward people and objects (anger-out). Key in this study was the finding that trait-anger temperament appeared as the best global predictor of paranoid beliefs, followed by external shame and depressive symptoms. Overall, these results may provide new perspectives on the nature of anger, highlighting the interrelationship between threat-defensive emotions and its impact on psychopathology.